Social and cognitive functions of music based on the example of Tuvan throat singing - Hsu, Shen-Mou (The New Research of Tuva, 2017)
Music is pervasive across human cultures and throughout times. Particularly, music serves great importance at social functions. Like many cultures’ use of music, throat singing or khöömei, the most distinguished aspect of Tuva’s music, contributes significantly to social communication, emotional expression, social bonding and religious rituals. Acknowledgment and consideration of current social cognitive findings of music may thus provide a better insight into the nature of throat singing. To date, evidence has indicated that similar to language, music is a fundamental channel of communication, and these two constructs may have common origins in a single communicative system. Moreover, music may modulate neural activity in the brain structures associated with emotions and alter our autonomic responses. In addition to information sharing, music thus has the capacity to convey emotions. This ability may further render music a powerful mechanism to facilitate social bonding and ritual practice, as individuals’ internal states during these social events become synchronized through musical engagement.In conclusion, I suggest that those social cognitive perspectives may point toward new directions for a continuing discourse on our understanding of throat singing.
Keywords: Tuva; Tuvans; music; throat singing; function of music